Improving Training of Modern Leaders Utilizing it in The Administration of The Higher Education System - Suyunovich, Temirov Ortiq; Fayzievna, Hakimova Muhabbat (Indonesian Journal of Teaching in Science, 2023)
This paper aims to discuss the problem of organizing students ' independent educational activities using IT projects and task management system. The concept of " independent learning activity " is formulated based on the studied domestic literature on this issue. The methodological potential of IT (e.g. the JIRA platform) is considered in the example of practical tasks of project management and organization of interaction between participants by analysing the functions of the program and correlating them with the tasks being implemented. The data obtained indicate the expediency of using the JIRA project and task management system as a means of implementing independent research -level learning activities when organizing a group project. The content of the research level of the system for improving independent learning activities is disclosed with consideration of preparatory measures and the first form of practical application, mastered and updated, which is a "group project ". The psycholinguistic content of independent learning activities of students at the level of higher education is analysed. The results of a methodical analysis of the JIRA project and task management system, which allows you to coordinate the interaction of users, students, project managers, and teachers are presented. A variant of preparing students for the group implementation of specialized linguistic independent educational activities by using the JIRA project and task management system is proposed.